Consumption of diclofenac and health outcomes in outpatients with or at high risk for cardiovascular diseases in Montenegro after implementation of the innovative risk minimization digital tool - Stanković, Maja; Turković, Nemanja; Dobrić, Silva; Rančić, Nemanja (Vojnosanitetski pregled, 2025)
Background/Aim. Risk minimization measures (RMMs) for medicines are one of the most important interventions in maintaining a positive benefit–risk ratio and ensuring their safe use. Systemic formulations of diclofenac are medicines with routine and additional RMMs in place for its well-established cardiovascular (CV) safety risk. In 2021, an innovative digital tool (IDT) was implemented in the Montenegrin Information System of Primary Health Care (PHCIS). The aim of this study was to analyze diclofenac consumption in CV risk patients who did not use diclofenac before the introduction of this new IDT for RMM (diclofenac-naïve patients), taking into account their demographic (gender and age) and clinical characteristics [CV diseases (CVD)/risk factors of CVD]. Methods. Patients with CVD/diseases posing a risk for CVD development (conditions that are contraindications/precautions for prescribing diclofenac) were selected after an automated screening of all diagnoses, classified in accordance with the International Classification of Diseases, 10th revision, from their electronic medical records. These patients also had medical diagnoses that served as indications for prescribing nonsteroidal anti-inflammatory drugs such as diclofenac. These patients were monitored for a period of one year after the introduction of the IDT (October 4, 2021 – October 4, 2022). Diclofenac consumption was analyzed using the standard methodology of the World Health Organization based on daily defined doses/1,000 inhabitants/day and the Anatomical Therapeutic Chemical classification of medicines, as well as the total number of prescriptions and prescribed packages of the drug, taking into account their gender, age, and high-risk CV diagnoses. Results. It was shown that diclofenac was prescribed more frequently to women and patients aged 45–64. Regarding medical diagnoses that are contraindications/precautions for diclofenac use, the drug was most often prescribed to patients with ischemic heart disease (38.15%) and hypertension (71.00%). Following the introduction of the drug into therapy, there was an increase in the number of patients with diagnoses (CVD) that are contraindications for diclofenac use. The largest increases were recorded in patients with diseases of arteries, small arteries and capillaries (41.77%), and congestive heart failure (28.57%). Conclusion. After the introduction of the IDT as a new RMM for adverse CV effects of diclofenac into the Montenegrin PHCIS, the drug was most frequently prescribed to female diclofenac-naïve patients, individuals aged 45–64 years, and those with high-risk CV diagnoses that required precautions for its use. The use of diclofenac led to an increase in the number of patients with CVD, indicating the need to introduce new measures to reduce the risk of its adverse CV effects.
Keywords: cardiovascular diseases; delivery of health care; diclofenac; drug prescriptions; drug utilization; montenegro; pharmacovigilance